Protective Effect of Testosterone against Gentamicin's Toxicity in Adult Male Rabbits - Moqbel, Fahmi S; Al Hamdani, Nada M. H.; Al-Shaibani, Elham A. S.; Qasem, Fadhl A. M.; Qasim, Mohammad Ahmed Ali Qasim; Al-Salami, Ahlam; Al-Kawli, Ameera; Al-Kawli, Eman; Al-Awadi, Ola'a (Thamar University Journal of Natural & Applied Sciences, 2025)
Background: Gentamicin is an effective aminoglycoside antibiotic widely used in clinical practice; however, its therapeutic application is often limited by adverse effects, particularly liver and kidney toxicity. Experimental evidence suggests that sex hormones may influence susceptibility to gentamicin-induced organ damage. Testosterone, in particular, has been proposed to exert a protective effect against such toxicity. Objective: This study evaluated the biochemical and histopathological changes in the liver and kidneys of adult male rabbits treated with gentamicin and testosterone, administered either alone or in combination. Methods: Twenty adult male rabbits were randomly assigned to four groups: a control group, a gentamicin-treated group (40 mg/kg body weight), a testosterone-treated group (15 mg/kg body weight), and a group receiving testosterone followed by gentamicin. Serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), urea, and creatinine were measured, and liver and kidney tissues were examined histologically. Results: Rabbits treated with gentamicin alone showed marked increases in serum ALT, AST, urea, and creatinine levels, indicating significant hepatic and renal injury. Administration of testosterone alone resulted in lower enzyme and metabolite levels compared with the gentamicin-treated group, suggesting limited organ stress. Co-administration of testosterone with gentamicin significantly reduced ALT and AST levels relative to gentamicin treatment alone, indicating partial hepatoprotection. However, urea and creatinine levels remained elevated, suggesting that the testosterone dose used was insufficient to prevent gentamicin-induced renal damage. Histopathological findings supported the biochemical results, with evident structural alterations in liver and kidney tissues following gentamicin exposure. Conclusion: Gentamicin induces pronounced hepatic and renal toxicity in adult male rabbits. Testosterone exerts organ-specific protective effects, providing partial protection to the liver but limited benefit to the kidneys under the conditions of this study.